Nutritional interventions for reducing the signs and symptoms of exercise-induced muscle damage and accelerate recovery in athletes: current knowledge, practical application and future perspectives - Bongiovanni, T.; Genovesi, F.; Nemmer, M.; Carling, C.; Alberti, G.; Howatson, G. (European Journal of Applied Physiology, 2020)
Purpose: This review provides an overview of the current knowledge of the nutritional strategies to treat the signs and symptoms related to EIMD. These strategies have been organized into the following sections based upon the quality and quantity of the scientific support available: (1) interventions with a good level of evidence; (2) interventions with some evidence and require more research; and (3) potential nutritional interventions with little to-no-evidence to support efficacy. Method: Pubmed, EMBASE, Scopus and Web of Science were used. The search terms `EIMD` and `exercise-induced muscle damage` were individually concatenated with `supplementation`, `athletes`, `recovery`, `adaptation`, `nutritional strategies`, hormesis`. Result: Supplementation with tart cherries, beetroot, pomegranate, creatine monohydrate and vitamin D appear to provide a prophylactic effect in reducing EIMD. â-hydroxy â-methylbutyrate, and the ingestion of protein, BCAA and milk could represent promising strategies to manage EIMD. Other nutritional interventions were identified but offered limited effect in the treatment of EIMD; however, inconsistencies in the dose and frequency of interventions might account for the lack of consensus regarding their efficacy. Conclusion: There are clearly varying levels of evidence and practitioners should be mindful to refer to this evidence-base when prescribing to clients and athletes. One concern is the potential for these interventions to interfere with the exerciserecovery-adaptation continuum. Whilst there is no evidence that these interventions will blunt adaptation, it seems pragmatic to use a periodised approach to administering these strategies until data are in place to provide and evidence base on any interference effect on adaptation.